Online intercultural exchange policy, pedagogy, practice - Lewis, Tim 1951-; O'Dowd, Robert 1972- (Routledge studies in language and intercultural communication, 2016)
This volume provides a state of the art overview of Online Intercultural Exchange (OIE) in university education and demonstrates how educators can use OIE to address current challenges in university contexts such as internationalisation, virtual mobility and intercultural foreign language education. Since the 1990s, educators have been using virtual interaction to bring their classes into contact with geographicalsly distant partner classes to create opportunities for authentic communication, meaningful collaboration and first-hand experience of working and learning with partners from other cultural backgrounds. Online exchange projects of this nature can contribute to the development of learner autonomy, linguistic accuracy, intercultural awareness, intercultural skills and electronic literacies